1998
DOI: 10.1136/bjo.82.5.498
|View full text |Cite
|
Sign up to set email alerts
|

Plasma endothelin-1 concentrations in patients with retinal vein occlusions

Abstract: Aims-To investigate whether plasma levels of endothelin-1 (ET-1), a potent vasoconstricting peptide that is crucial in regulating retinal blood flow, were elevated in patients with retinal vein occlusion (RVO). Methods-ET-1 plasma concentrations were determined by radioimmunoassays in a double blind fashion in a group of 18 selected patients with RVO, in 20 healthy age matched non-smoking, normoglycaemic, normotensive control subjects, and in 15 patients with uncomplicated essential hypertension in the same ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 32 publications
(25 reference statements)
1
36
0
2
Order By: Relevance
“…Iannaccone et al [37] reported significantly increased circulating endothelin-1 plasma levels in patients with RVO compared with healthy controls and patients with essential hypertension in the same age range. Circulating endothelin-1 levels were higher in patients with the ischemic type of RVO (three BRVO and four CRVO) than non-ischemic RVO (six BRVO and five CRVO).…”
Section: Miscellaneousmentioning
confidence: 96%
“…Iannaccone et al [37] reported significantly increased circulating endothelin-1 plasma levels in patients with RVO compared with healthy controls and patients with essential hypertension in the same age range. Circulating endothelin-1 levels were higher in patients with the ischemic type of RVO (three BRVO and four CRVO) than non-ischemic RVO (six BRVO and five CRVO).…”
Section: Miscellaneousmentioning
confidence: 96%
“…The 21 amino acid peptide endothelin-1 (ET-1) is synthesized by retinal arterioles to exert vasoconstriction, predominantly via endothelin type A (ET A ) receptor activation. 2 Elevated vitreous and/or plasma levels of ET-1 are associated with several important retinal diseases, including retinal vein occlusion, 3 open angle glaucoma, 4 and diabetic retinopathy, 5,6 and ET-1 may contribute, in part, to these pathologies through its activity as a vasoconstrictor. On the other hand, ET-1 also can activate endothelial ET type B (ET B ) receptors to exert vasodilation via released nitric oxide (NO).…”
mentioning
confidence: 99%
“…17,18 This is the reason why an increased level of ET in the circulating blood (as can be observed in many different autoimmune diseases such as multiple sclerosis) has a major effect on optic nerve head circulation but no or only a minimal effect on retinal or brain circulation. An increased level of ET seems to be implicated in the pathogenesis of many ocular diseases, particularly retinal vein occlusion, 19,20 glaucoma, 21 diabetic retinopathy, 22 and giant cell arteritis. 23 Although ET obviously plays an important role, many basic aspects of its function are still poorly understood, including the question of the dose-response relationship.…”
Section: Introductionmentioning
confidence: 99%